1974
DOI: 10.1080/11250007409430120
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Colored Substrates for Oviposition inDrosophila Melanogaster

Abstract: The choice of oviposition sites in females of Drosophila is the result of comples behavior patterns which can be modified by a number of factors. Among these, the presence of eggs or larvae induces other females to oviposit in the dame place. The relative size of the population and the coexistence with females of a diffcrcnt spccics arc some of the other environmental variables involved (DEL SOLAR and PALomxo, lDGG, 1071 ; DEL .SOLAR and GODOY, 1073). Other factors may be resolved on the a decision making D of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…While our results suggest that both mating states strongly relied on fruit‐derived odours for long‐range attraction, the short‐range olfactory preference for oviposition substrates has been found to be mediated through a single olfactory channel in which apple and banana odours induce very similar physiological responses (Dweck et al ). Moreover, as other studies have shown that oviposition behaviour is governed by a combination of olfactory (Ruebenbauer et al , Dweck et al , Hussain et al ), visual (Del Solar et al ) and gustatory information (Clyne et al , Thorne et al ), we expect that the change in the use of short‐range cues and the lack of additional sensory cues lowered the interest of the mated females to select among our odour sources (Supplementary material Appendix 1 Fig. , Table A3), and eventually removed the competitive interactions between apple and banana odour sources in our mixed resource environments (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…While our results suggest that both mating states strongly relied on fruit‐derived odours for long‐range attraction, the short‐range olfactory preference for oviposition substrates has been found to be mediated through a single olfactory channel in which apple and banana odours induce very similar physiological responses (Dweck et al ). Moreover, as other studies have shown that oviposition behaviour is governed by a combination of olfactory (Ruebenbauer et al , Dweck et al , Hussain et al ), visual (Del Solar et al ) and gustatory information (Clyne et al , Thorne et al ), we expect that the change in the use of short‐range cues and the lack of additional sensory cues lowered the interest of the mated females to select among our odour sources (Supplementary material Appendix 1 Fig. , Table A3), and eventually removed the competitive interactions between apple and banana odour sources in our mixed resource environments (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…It is important because oviposition sites in nature vary in quality, affecting fitness of offspring. In the genus Drosophila, many factors influence OSS, including texture of the medium (David, 1970;Rockwell and Grossfield, 1978), color of the substrate (Carfagna and Lancieri, 1971;del Solar et al, 1974), gregariousness (del Solar and Palomino, 1966), larval conditioning of the medium (Dawood and Strickberger, 1969;Weisbrot, 1966), larval density (Lewontin, 1955), and competitive interactions between species (Barker, 1971;McKenzie and Parsons, 1972;Soliman, 1971). The adaptive nature of OSS is clear for some of these factors, especially in the case ofintra-and interspecific competition.…”
mentioning
confidence: 99%
“…The nociceptive system mediates ovipositional avoidance in response to capsaicin. Drosophila ranks egg-laying sites via sensory modalities 22 , including vision 23 , gustation 24 , olfaction 14 , and nociception 25 . Next, we attempted to identify potential sensory modalities responsible for the ovipositional aversion to capsaicin.…”
Section: Resultsmentioning
confidence: 99%